2015
DOI: 10.1016/j.nucmedbio.2015.06.010
|View full text |Cite
|
Sign up to set email alerts
|

PET imaging of TSPO in a rat model of local neuroinflammation induced by intracerebral injection of lipopolysaccharide

Abstract: The LPS model is useful for first screening of newly developed tracers because of the easy design and the robust, unilateral inflammatory reaction allowing the use of the contralateral region as control. Additionally, this model can be used to test and follow up the benefits of anti-inflammatory therapies by non-invasive imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
48
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 18 publications
5
48
0
Order By: Relevance
“…In a rat model of neuroinflammation induced by intracerebral injection of lipopolysaccharides, the area of microglial activation corresponded TSPO in vitro binding whereas the area of astroglial activation was considerably smaller than, albeit still located within, the area of TSPO binding (18). In the same animal model, double immunostaining revealed prominent TSPO expression by reactive microglia and low levels of TSPO expression by reactive astrocytes (33). Activated microglia and astroglia were both found to express TSPO in a rat model of stroke; however, the PET-derived time profile of in vivo TSPO expression corresponded to microglial and not astroglial activation (34).…”
Section: Discussionmentioning
confidence: 85%
“…In a rat model of neuroinflammation induced by intracerebral injection of lipopolysaccharides, the area of microglial activation corresponded TSPO in vitro binding whereas the area of astroglial activation was considerably smaller than, albeit still located within, the area of TSPO binding (18). In the same animal model, double immunostaining revealed prominent TSPO expression by reactive microglia and low levels of TSPO expression by reactive astrocytes (33). Activated microglia and astroglia were both found to express TSPO in a rat model of stroke; however, the PET-derived time profile of in vivo TSPO expression corresponded to microglial and not astroglial activation (34).…”
Section: Discussionmentioning
confidence: 85%
“…44,45 Animal studies have shown that the TSPO signal in brain is mainly derived from microglia, 20,46 with a significant contribution from astrocytes during certain conditions. 19,47 Apart from these resident immune cell populations, peripherally derived myeloid cells in the form of infiltrating or perivascular macrophages may also contribute to the signal.…”
Section: Discussionmentioning
confidence: 99%
“…Arterial blood was sampled using an automated system for the first 5 minutes. Manual samples were drawn at 2, 4,6,8,10,15,20,25,30,45, and 60 minutes. All patients were genotyped for the genetic polymorphism of rs6971, which affects binding of TSPO radioligands, including [ 11 C]PBR28, both in vitro and in vivo.…”
Section: Pet Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…Using positron emission tomography (PET), the localization and activation state of central nervous system immune response modulators can be assessed with radioligands targeting the 18-kDa translocator protein (TSPO), which is expressed in glial cells (7)(8)(9). During the last decade, a handful of TSPO PET studies have been performed in patients with early-stage psychosis or manifest schizophrenia, showing inconclusive results.…”
mentioning
confidence: 99%